论电视剧《后宫・甄嬛传》中的女性古典美 = Discourse on the ancient beauty portrayed in the Chinese drama empresses in the palace - 荆思凡 Jing, Sifan (Nanyang Technological University, 2017)
古装剧在中国的影视圈占有一席之地，其中宫廷剧更是为人们所热爱。大型宫廷剧《后宫・甄嬛传》的热播标志着中国影视的一大成功。 在人们纷纷追随"甄嬛热"的背后是对中华文化的认可。《后宫・甄嬛传》的成功不仅仅依靠精彩的剧情，美轮美奂的舞蹈、极具考究的服装装扮和古风浓烈的人物对白都赋予每個女性角色独特的古典美。本文将着重探讨在这部电视剧中，古典美是如何被建构的，以及古典美的背后又依附着什么。 Costume drama has always been influential in the Chinese show business. Court drama is one of most popular topic among the rest. The wide broadcasting of the drama Empresses in the Palace is the epitome of success in the Chinese drama industry. The fact that there are people fervently following the Zhenhuan Heat shows that there is a significant level of recognition and support of the Chinese culture in the modern era. On top of its fantastic plot, the drama showcases fascinated dance, sophisticated costumes and fabulous accessories. Moreover, the dialogues in the drama are also full of rich Chinese culture, further illustrating the sense of ancient beauty as portrayed by the female characters. This thesis aims to discuss how ancient beauty is constructed, as well as what is associated with it, through analyzing the drama.